Portrayal of Disability in Textbooks A Psycho-educational Perspective - Kaur, Ravneet (JOURNAL OF INDIAN EDUCATION, 2015)
The Constitution of India guarantees equal rights for all citizens. The Right to Education (RTE) Act (2009) made elementary education a fundamental right of every child, including children with disabilities. The education system works as an apparatus in furthering the ideological stand of the state. Since textbooks dominate the educational process and occupy a significant position within the Indian education culture; textbooks thus become the ‘tools’ to achieve constitutional, legal and social goals through education. The present paper aims to critically analyse the portrayal of persons with disabilities in textbooks used in elementary schools. The paper closely analyses the depictions of the issues and concerns pertaining to disability. The paper examines the themes, plots and contexts of the lessons. It further builds the characters of the persons with disabilities and the views and attitudes of other characters towards them. The paper locates these within psycho-educational perspectives.